Efficacy of Management Practices to Mitigate the Off-Site Movement and Ecological Risk of Pesticides Transported with Runoff from Agricultural and Turf Systems - Rice, Pamela J.; Horgan, Brian P.; Hapeman, Cathleen J.; McConnell, Laura L. (IntechOpen, 2011)
None